Evaluation of The Use Antituberculosis Drugs and Analysis of Adherence Pulmonary Tuberculosis Patients at The Sidomulyo Health Center, Pekanbaru - Denia Pratiwi; Maisarah Maisarah; Deri Islami (Jurnal Ilmu Kesehatan Abdurrab, 2023)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis. Based on data from the Global Tuberculosis Report in 2022, Indonesia ranks as the second highest TB case after India. This study aims to evaluate the suitability of OAT use in pulmonary tuberculosis patients at the Sidomulyo pekanbaru Health Center from January-December 2022 based on the 2014 Tuberculosis Prevention guidelines by the Ministry of health of the Republic of Indonesia, as well as the relationship between age, duration of treatment,gender, and chronic comorbidities to patient treatment outcomes,and analysis of the level of adherence of pulmonary TB patients. This study is a non-experimental descriptive research with retrospective data retrieval. The results showed that the type of OAT given is OAT type KDT (fixed dose combination) of 99% with a cure rate of 80%. Suitability of indications, dosage and selection of OAT combination has been in accordance with the standards of the National TB guidelines in 2014. Analysis of the relationship between several factors on the results of treatment of patients obtained from the statistical analysis of chi-square test concluded that the age factor (p=0.00001;p<0.05) has a significant relationship while gender (p=0.064;p>0.05), duration of treatment (p=0.860;p>0.05) and chronic comorbidities (p=0.826;p>0.05) had no significant relationship to the patient's treatment outcomes. The level of patient compliance obtained from the results of filling out questionnaires for pulmonary TB patients at the Sidomulyo Health Center has a high compliance of 49%.